2022
DOI: 10.1021/acs.inorgchem.1c03339
|View full text |Cite
|
Sign up to set email alerts
|

Iron(II) Immobilized within a Metal–Organic Framework Mixed-Matrix Membrane as a H2O2 Turn-On Sensor

Abstract: H 2 O 2 detection is closely relevant to human health; however, most of the H 2 O 2 probes suffer from low accuracy and sensitivity because of the aggregating nature of solid sensors. In contrast, a mixed-matrix membrane (MMM) with high processability and flexibility is a suitable H 2 O 2 probe to overcome these drawbacks. Herein, we fabricated MOF-based MMMs by using a robust UiO-66-(COOH) 2 with carboxylate-chelating moieties, which were utilized for binding Fe (II) metal centers. The Fe (II)-immobilized MOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Every functional nanoparticle of UiO‐66‐(COOH) 2 contained twelve linkers, and every linker contained two free uncoordinated −COOH groups. The −COOH on the framework could provide a binding site for the adsorption of Sr 2+ ions 35 . In order to explore the crystal structure of the prepared UiO‐66‐(COOH) 2 , a sample was investigated using XRD, and the XRD pattern is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Every functional nanoparticle of UiO‐66‐(COOH) 2 contained twelve linkers, and every linker contained two free uncoordinated −COOH groups. The −COOH on the framework could provide a binding site for the adsorption of Sr 2+ ions 35 . In order to explore the crystal structure of the prepared UiO‐66‐(COOH) 2 , a sample was investigated using XRD, and the XRD pattern is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The −COOH on the framework could provide a binding site for the adsorption of Sr 2+ ions. 35 In order to explore the crystal structure of the prepared UiO-66-(COOH) 2 , a sample was investigated using XRD, and the XRD pattern is shown in Fig. 2(a).…”
Section: Dynamic Separation Experimentsmentioning
confidence: 99%
“…Yang et al reported an extremely stable Eu-MOF with excellent selectivity and cycling performance as a luminescence probe for ether vapor . In addition, to achieve fast and flexible detection in a wider range of application scenarios, mixed-matrix membranes (MMMs) based on fluorescent MOF sensors have recently received significant attention. For instance, Qin et al reported that a Zn-MOF with mixed nodes was not easily destroyed under organic solvents and acid–base conditions, and the luminescence capacity was stable. In aqueous solution, the membrane composed of the MOF also efficiently detects Fe 3+ , CrO 4 2– , and Cr 2 O 7 2– .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12] In recent years, MOFs based conductive composites for electrochemical detection have made significant progress, however, these MOFs electrochemical sensors were commonly based on powder samples and there were the following limitations: (1) powder samples were easy to fell off from electrodes during electrochemical sensing processes, resulting in low sensitivity and inaccuracy; (2) powder sensors were expected to be assembled into devices materials for further practical applications; (3) the inherent rigidity nature of MOFs materials inhibited their processability. [13][14][15][16][17] These shortcomings became critical barriers for manipulation and hampered further practical applications as electrochemical sensors. As a result, the exploration of MOFs-based electrochemical sensing devices via simple methods remained a necessary task.…”
Section: Introductionmentioning
confidence: 99%